Effects of Progressive Mobilization on Hemodynamic Status of Bedridden Patients in the Intensive Care Unit (ICU) - A.A Istri Dalem Hana Yundari; Ni Luh Putu Thrisnadewi; Ni Made Nopitawati (Jurnal Keperawatan Respati Yogyakarta, 2023)
Patients treated in ICU generally last for an extended period due to the severity of the patient’s suffering. One of the efforts made by nurses to improve the functional and hemodynamic status of patients is to mobilize. Progressive mobilization given to the patient is expected to cause an excellent hemodynamic response. In the upright sitting position, the performance of the lungs, both in the distribution of ventilation and perfusion, will improve during mobilization. This study contributed to knowing the effectiveness of progressive mobilization on hemodynamic status in bedridden patients in the ICU. The design used Pre-Experiment research with one group pre-test and post-test design. Thirty samples were selected in the ICU for 21 days. Data analysis used Paired T-Test analysis. There is an effect of progressive mobilization on the hemodynamic status of patients in ICU (pulse: p-value 0.000, respiratory rate p-value 0.000, systolic blood pressure p-value 0.000, diastolic blood pressure p-value 0.004, MAP p-value 0.000, and SaO2 p-value 0.000). There is an effect of progressive mobilization on the hemodynamic status of patients in the ICU. It is expected that nurses and physiotherapists in hospitals would continue to apply progressive march in an effort to overcome the problem of hemodynamic disorders in the ICU